1981
DOI: 10.1073/pnas.78.3.1490
|View full text |Cite
|
Sign up to set email alerts
|

N-Methylprotoporphyrin IX: chemical synthesis and identification as the green pigment produced by 3,5-diethoxycarbonyl-1,4-dihydrocollidine treatment.

Abstract: The hepatic pigment accumulated in 3,5-diethoxycarbonyl-1,4-dihydrocollidine-treated rats, which has been reported to inhibit ferrochelatase, has been isolated and purified. The pigment has been resolved into one major, one minor, and two trace components, all of which appear to be isomeric porphyrins. The major fraction has been unambiguously identified byspectroscopic methods as the isomer of N-methyprotoporphyrin IX (isolated as the dimethyl ester) in which vinyl-substituted pyrrole ring A is methylated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 20 publications
(36 reference statements)
1
30
0
Order By: Relevance
“…5. These spectra are like those of other N-substituted porphyrin derivatives (14,16,17). Similar spectra were obtained with green pigment IV.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…5. These spectra are like those of other N-substituted porphyrin derivatives (14,16,17). Similar spectra were obtained with green pigment IV.…”
Section: Resultssupporting
confidence: 69%
“…The signals of the methylene protons adjacent to the pyrrole ring (6 4.10-4.40) are broadened, and the signals of the methylene protons adjacent to the ester group are separated at chemical shifts of 2.82 and 3.08. These results suggest that the phenyl group is attached to one ofthe two pyrrole rings with a propionic acid methyl ester substituent (14,15).…”
Section: Resultsmentioning
confidence: 79%
“…The electronic absorption spectrum of the Zn N-alkylPP dimethyl ester in dichloromethane (1.0 ml) was determined, and the Zn N-alkylPP dimethyl ester concentration was calculated using the molar extinction coefficient of 128,000 m Ϫ1 cm Ϫ1 at 432 nm (Ortiz de Montellano et al, 1981b). The dichloromethane solution (1.0 ml) was diluted with 1.0 ml of dichloromethane, and the fluorescence spectrum of the Zn N-alkylPP dimethyl ester in dichloromethane was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Two antipodes are therefore possible for each N-methyl protoporphyrin, depending upon whether the N-methyl group lies above or below the porphyrin plane. Preliminary observations have suggested that the N-methyl protoporphyrin isolated from the liver after treatment with DDC is optically active [21,22]. In contrast, synthetic N-methyl protoporphyrin is opticaUy inactive, as it is a racernic mixture of the 2 enantiomorphs.…”
Section: Chirality Of N-monosubstituted Protoporphyrinsmentioning
confidence: 99%